FAKTOR- FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN PADA USAHA PENJAHIT NOVA DI KABUPATEN MIMIKA - Jaya Heatubun; Rulan L. Manduapessy (CV. ADIBA AISHA AMIRA, 2023)
The purpose of this research is how to increase consumer satisfaction with Nova's sewing business in Mimika Regency. Data collection techniques used to obtain data in this study were interviews, questionnaires, observation and documentation. The analysis used in this study is a multiple linear regression technique. The results of this study were to find out whether product quality, service quality, price and warranty really influence consumer satisfaction in Nova tailoring businesses in Mimika Regency through the percentage increase in stitch quality in Nova tailoring businesses